Automatic target detection and localization using ultra-wideband radar - Dounia Daghouj; Marwa Abdellaoui; Mohammed Fattah; Said Mazer; Youness Balboul; Moulhime El Bekkali (International Journal of Electrical and Computer Engineering (IJECE), 2022)
The pulse ultra-wide band (UWB) radar consists of switching of energy of very short duration in an ultra-broadband emission chain, and the UWB signal emitted is an ultrashort pulse, of the order of nanoseconds, without a carrier. These systems can indicate the presence and distances of a distant object, call a target, and determine its size, shape, speed, and trajectory. In this paper, we present a UWB radar system allowing the detection of the presence of a target and its localization in a road environment based on the principle of correlation of the reflected signal with the reference and the determination of its correlation peak.